Health impacts of long-term ozone exposure in China over 2013–2017. (November 2020) - Wang, Yuanlin; Wild, Oliver; Chen, Xueshun; Wu, Qizhong; Gao, Meng; Chen, Huansheng; Qi, Yi; Wang, Zifa
Highlights: New relative risk estimates used to assess health impacts in China due to O3 . Key model-simulated O3 metrics were bias-corrected with observations. 186, 000 respiratory deaths annually attributable to long-term ozone exposure. National premature respiratory deaths increased by 31% from 2013 to 2017. Abstract: Increasing ozone concentrations are becoming a severe problem for air pollution in China and have an adverse impact on human health. Here we evaluate premature deaths attributable to long-term exposure to ambient ozone in China between 2013 and 2017 with an air quality model at 5 km resolution and the latest estimates of the relative risk to health. We use a modified inverse distance weighting method to bias-correct the key model-simulated ozone metrics. We find that on a 5-year average basis there are 186, 000 (95% Confidence Interval: 129, 000–237, 000) respiratory deaths and 125, 000 (42, 000–204, 000) cardiovascular deaths attributable to ozone exposure. Sichuan exhibits the largest per capita respiratory mortality (0.31‰) among all provinces. We find that there are 73, 000 (51, 000–93, 000) premature respiratory deaths in urban areas, accounting for 39% of total deaths. Between 2013 and 2017 the population-weighted annual average maximum daily 8-h average ozone (AMDA8) and premature respiratory deaths increased by 14% and 31%, respectively, at a national level. Changes in precursor emissions explain most of these increases, with differences in meteorology accounting for 21% and 16% respectively. Interannual variations in population-weighted ozone and premature respiratory deaths at a provincial level are much larger than those at a national level, particularly in northern, central and eastern China. These findings emphasize that ozone should be an important focus of future air quality policies in China, and tighter controls of precursor emissions are urgently needed.